Design of an integrated system for the vehicular traffic light control in Huánuco urban area - Huapaya-Condori, Freddy R. (2019)
The main aim of this research was to make a design for an Integrated Traffic Light Control plan in Huánuco urban area in order to reduce the time for transportation and traffic jams. In this way, we realized a diagnostic in order to identify the most critical points about the traffic jam into our city. We also have identified many problems because of the disorder in the traffic signals and the lack of respect to the regulations and municipal ordinances. We also add the lack of a technical study in order to make a proper installation of those traffic lights, which the municipality installs without having priorities of synchronization among them, so that the citizens spend more time in transport. That is the why we are considering the design of an Integrated traffic light control system. This research has an intention to find all the resources that our city has about this problem, such as its infrastructure, traffic ordinances and laws in order to improve all these problems.